P48 Research BAL using single use disposable bronchoscope. (15th November 2016) - Zaidi, S; Collins, A; Davies, K; Wright, A; Ganguli, A; Mitsi, E; Reine, J; Owugha, J; Gordon, S; Ferreira, D; Rylance, J
Abstract : Background: Broncho alveolar lavage (BAL) is widely used for investigative research to study innate, cellular and humoral immune responses, and in early phase drug trials. Conventional (multiple use) flexible bronchoscopes have time and monetary costs associated with cleaning, and may also carry a small risk of cross infection. Single use bronchoscopes may provide an alternative, but have not been evaluated in this context. Methods: Healthy volunteers underwent bronchoscopy on a day-case clinical research unit using the Ambu® Scope single-use flexible intubation bronchoscope. The bronchoscopy protocol was identical to previous studies using multiple-use equipment: fasted volunteers had local anaesthesia to the nasopharynx, and were intubated with further sequential local anaesthetic (2% lidocaine throughout). Lavage was performed from a sub segmental bronchus within the right middle lobe. A total of 200ml of warmed normal saline divided into four aliquots. Fluid was aspirated using handheld suction. Supplemental oxygen was used to maintain saturations above 90% throughout the procedure. The lab processing of BAL was identical to earlier studies. BAL volume was recorded, mucus plugs removed by filtration through a double layered gauze swab into sterile centrifuge tubes. The cells were pelleted by centrifugation and washed by vortexing in 50 mls of cold normal saline, then re-suspended in culture medium for differential counting and viability staining with trypan blue stain. Results: Ten volunteers, (mean age 23 years, 6 male) participated. The procedure was well tolerated by all the participants and all were carried out by two operators. The results were compared to 50 (mean age 23, 14 male) procedures done using the conventional scope by the same two operators. The total volume yield was significantly higher in the disposable group mean (SD) 149 mls (24.6) compared to 123 mls (20.6) p = 0.0007 Mann-Whitney Test. The total cell yield and viability were similar in both groups, with no significant differences. Conclusions: BAL using single use bronchoscopes are safe with no risk of cross infection, and well tolerated, with potentially reduced side effects post procedure such as pleuritic chest pain and cough as the volume yield is better. The cell yield and viability are comparable to the conventional bronchoscopes.